2017
DOI: 10.1111/psyp.13043
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness, resting state heart rate, and heart rate variability in female adolescents

Abstract: Resting state heart rate variability (HRV) is a psychophysiological marker that has gained increasing research interest, in particular in developmental neuroscience. HRV has been shown to be associated with mental and physical health, beyond simple measures of heart rate (HR) and shows inter- and intraindividual variance across aging. Recently, three studies reported on a positive correlation between resting state HRV and cortical thickness in selected regions of interest (ROIs) in adult samples. Structural th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…The significant cross-over interaction suggests that in subjects with lower depressive symptoms, lower right insula cortical thickness was associated with greater RVA. This finding is in line with prior research in non-depressed adolescents, illustrating that greater RVA is associated with reduced cortical thickness in subjects of younger age (Koenig et al 2018), contrary to a positive association reported in adults (Woodward et al , 2008; Winkelmann et al , 2016; Yoo et al , 2018). The prior study in adolescents did not support an association between insula thickness and RVA, but highlighted the rostral ACC in models not controlling for depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The significant cross-over interaction suggests that in subjects with lower depressive symptoms, lower right insula cortical thickness was associated with greater RVA. This finding is in line with prior research in non-depressed adolescents, illustrating that greater RVA is associated with reduced cortical thickness in subjects of younger age (Koenig et al 2018), contrary to a positive association reported in adults (Woodward et al , 2008; Winkelmann et al , 2016; Yoo et al , 2018). The prior study in adolescents did not support an association between insula thickness and RVA, but highlighted the rostral ACC in models not controlling for depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…While the causality in the link between cortical thickness and RVA is unclear, we have previously suggested that greater RVA might be beneficial for cortical thinning during adolescence (Koenig et al 2018). Considering environmental influences, lower RVA may be a consequence of increased stress and in turn is associated with greater stress vulnerability in children and adolescents (Porges, 1992; Michels et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations